2016
DOI: 10.1136/bmjopen-2016-011316
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' assessments of work capacity in patients with severe subjective health complaints: a cross-sectional study on differences between five European countries

Abstract: ObjectivesA comparison of appraisals made by general practitioners (GPs) in France and occupational physicians (OPs) and insurance physicians (IPs) in the Netherlands with those made by Scandinavian GPs on work capacity in patients with severe subjective health complaints (SHCs).SettingGPs in France and OPs/IPs in the Netherlands gathered to watch nine authentic video recordings from a Norwegian general practice.Participants46 GPs in France and 93 OPs/IPs in the Netherlands were invited to a 1-day course on SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…In the Netherlands, the employer is obliged to pay the salary of the sick employee for 2 years after the start of sick leave. The rate of return to work of 67·5 per cent at 2 years after the start of the sick leave in the present study is comparable to results in other countries (60–83 per cent).…”
Section: Discussionsupporting
confidence: 87%
“…In the Netherlands, the employer is obliged to pay the salary of the sick employee for 2 years after the start of sick leave. The rate of return to work of 67·5 per cent at 2 years after the start of the sick leave in the present study is comparable to results in other countries (60–83 per cent).…”
Section: Discussionsupporting
confidence: 87%
“…A plausible explanation for this rather paradoxical finding can be related to the question used to measure presenteeism. By asking physicians who had gone to work with an illness if they would have recommended that a patient stay home, the question used to measure presenteeism may have confounded national differences with sick-listing practices (Werner et al, 2016). Although limited to patients with severe subjective health complaints, the study by Werner et al (2016) demonstrated that Norwegian physicians grant sick leave to patients more often than do Swedish physicians.…”
Section: Discussionmentioning
confidence: 99%
“…By asking physicians who had gone to work with an illness if they would have recommended that a patient stay home, the question used to measure presenteeism may have confounded national differences with sick-listing practices (Werner et al, 2016). Although limited to patients with severe subjective health complaints, the study by Werner et al (2016) demonstrated that Norwegian physicians grant sick leave to patients more often than do Swedish physicians. By illustrating how structures in the broader social environment can influence studies on presenteeism, this highlights the relevance of differentiating estimates by respondents' nationality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences may be even more noticeable among physicians with different medical expertise or working in different settings with different frames of reference (such as national policies), or with different tasks and roles. A previous study reported that physicians from different European countries indeed differ in the outcome on sick leave assessments of workers with subjective health complaints [21]. This study compared the outcome of sick leave assessments of GPs from Sweden, Norway, Denmark and France, with insurance physicians and occupational physicians in the Netherlands [21].…”
Section: Introductionmentioning
confidence: 94%